1987
DOI: 10.1038/326517a0
|View full text |Cite
|
Sign up to set email alerts
|

Functional identity of proliferating cell nuclear antigen and a DNA polymerase-δ auxiliary protein

Abstract: The mechanism of replication of the simian virus 40 (SV40) genome closely resembles that of cellular chromosomes, thereby providing an excellent model system for examining the enzymatic requirements for DNA replication. Only one viral gene product, the large tumour antigen (large-T antigen), is required for viral replication, so the majority of replication enzymes must be cellular. Indeed, a number of enzymatic activities associated with replication and the S phase of the cell cycle are induced upon SV40 infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
483
0
8

Year Published

1993
1993
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,044 publications
(505 citation statements)
references
References 24 publications
10
483
0
8
Order By: Relevance
“…7 On the other hand PCNA is also a non-histone nuclear protein and is present in the late G1 phase, with the peak in G1/S interphase of the cell cycle. 9 As the two markers indicate the different cell cycle phases of proliferating cell, we use both of them. In several studies the determination of proliferating activity and Ki-67 antigen proved to be a useful parameter to distinguish between benign and malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…7 On the other hand PCNA is also a non-histone nuclear protein and is present in the late G1 phase, with the peak in G1/S interphase of the cell cycle. 9 As the two markers indicate the different cell cycle phases of proliferating cell, we use both of them. In several studies the determination of proliferating activity and Ki-67 antigen proved to be a useful parameter to distinguish between benign and malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…PCNA is normally localized in the nucleus as an essential component of the replication mechanism (Bravo et al, 1987;Prelich et al, 1987). Besides its role in replication, it is directly involved in nucleotide excision repair (Shivji et al, 1992), and elevated expression is detected in response to DNA damage in vivo (Hall et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular cloning of p125 showed that the catalytic core was highly conserved in evolution from T4 bacteriophage to human Hao et al, 1992;Yang et al, 1992], and Pol d is now classified as a member of the B family polymerases. Closely allied with the early history of Pol d are studies of the eukaryotic DNA-sliding clamp, proliferating cell nuclear antigen (PCNA; [Kuriyan and O'Donnell, 1993;Moldovan et al, 2010]), which was discovered as a processivity factor that stimulated Pol d activity [Prelich et al, 1987].…”
Section: Introductionmentioning
confidence: 99%